English learners with learning disabilities : a collaborative practice guide for educators - Boon, Richard T.; Spencer, Vicky G. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"This edited book is intended to offer a practical guide for general, special, and bilingual/English as a second language educators working with English learners (ELs) with learning disabilities in the K-12 inclusive classroom. Authored by leading scholars with expertise in the fields of special and bilingual education, the book provides educators with a solid foundation of the growing demographics of ELs in our schools, an understanding of second language acquisition, further knowledge of the referral, assessment, and identification process, including the individualized education program, legal issues, instructional practices, and multi-tiered systems of support, research-based interventions, with a specific focus on reading, a variety of co-teaching models, and ways to better communicate with parents and/or families to enhance collaboration between home and school"-- Provided by publisher.
Keywords: English language -- Study and teaching -- Foreign speakers.; Education, Bilingual -- United States.; Learning disabled children -- Education (Elementary) -- United States.; Learning disabled teenagers -- Education (Secondary) -- United States.; Inclusive education -- United States.; Education -- Special Education -- Learning Disabilities.; For specific learning difficulties.; Teaching of students with learning difficulties.; Relating to people with learning disorders, difficulties or disabilities.; elektronické knihy; electronic books